2015
DOI: 10.1016/j.mambio.2015.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effects of forest structure on the small mammal community in frequent-fire coniferous forests using capture-recapture models for stratified populations

Abstract: Please cite this article as: Sollmann, R., White, A.M., Gardner, B., Manley, P.N.,Investigating the effects of forest structure on the small mammal community in frequent-fire coniferous forests using capturerecapture models for stratified populations, Mammalian Biology (2015), http://dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…For each of the target species, we considered consistent site‐specific divergences from the average adult sex ratio (male:female), juvenile to adult ratio (juvenile:adult), and average adult body mass (either the highest or lowest among all years) as evidence of an abnormal population structure, which might reflect differences in habitat quality (Greenberg et al , Robertson and Hutto , Sollmann et al ). Species‐specific adult sex ratios were the number of known adult males divided by the number of known adult females caught on each site within a year, and juvenile to adult ratios were the number of known juveniles divided by the number of known adults.…”
Section: Methodsmentioning
confidence: 99%
“…For each of the target species, we considered consistent site‐specific divergences from the average adult sex ratio (male:female), juvenile to adult ratio (juvenile:adult), and average adult body mass (either the highest or lowest among all years) as evidence of an abnormal population structure, which might reflect differences in habitat quality (Greenberg et al , Robertson and Hutto , Sollmann et al ). Species‐specific adult sex ratios were the number of known adult males divided by the number of known adult females caught on each site within a year, and juvenile to adult ratios were the number of known juveniles divided by the number of known adults.…”
Section: Methodsmentioning
confidence: 99%
“…Despite continued forest destruction in Uganda, few studies have directly examined the effects of disturbance on small mammal communities. Sollmann et al (2015) found forest structure to influence total abundance of species and abundance of some individual species. Some of the major disturbances in Afro-tropical forest ecosystems are human mediated (Obua et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The reduced vegetation complexity of closed-canopy forests may limit resources important to small mammals. Most studies show that forests with a greater percentage of tree cover harbour less abundant small mammal communities 44 . In the Sierra Nevada mountains in North America, small mammals showed a limited response to canopy thinning, reflecting the generalist habits of the common species in those forests, which may be a legacy of more than a century of human impacts generating a process of biotic homogenization via differential success of some native species over the others 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Unlike rocks, woody debris is more ephemeral, and apparently it was less valued as a shelter resource (Table 3 ). Many studies show the importance of coarse woody debris as a quantitative habitat feature for forest small mammals 44 ; their value increases in the late decay stages 52 . Woody debris in mid-to-late decay state is often a suitable substrate for lichen and fungi, and can support a rich insect fauna 53 , all potential foods for omnivorous rodents and shrews.…”
Section: Discussionmentioning
confidence: 99%